Construction systems, integrated disaster risk management & climate change adaptation - Tiktik Kaanu indigenous community (Nexo Revista Científica, 2023)
The Caribbean Coast of Nicaragua is a pluricultural and multilingual region where diverse cultures coexist: Miskito, Sumu-Mayangna and Rama indigenous peoples, Afro-descendant Kriol and Garifuna communities and mestizo communities. This makes the Caribbean one of the richest areas in terms of cultural diversity and identity. It is a fact that the acceleration of climate change variability is a global problem that affects everyone, but differently and that its effects are evident in Nicaragua and mainly in the Caribbean Coast and these will begin to impact many aspects of life. The native peoples and ethnic communities of the region face particular vulnerabilities and risks in the face of the threats caused by climate change. The causes and consequences are understood in different ways, depending on the vision of nature that different cultures have, ranging from perceptions of changes in the environment to predict weather and climate fluctuations to highly described and orally documented variations in climate patterns. The ethnographic study in the Tiktik Kaanu community, Bluefields Municipality, South Coast Autonomous Region, Republic of Nicaragua, aims to describe the ethnicity, culture and construction systems in disaster risk conditions in the community of Tiktik Kaanu, located 42 kilometers south of Bluefields on the banks of the Kukra River, as part of the research and extension sections of the referred subproject.